Il comunista solo e la sua luce. Un’indagine sulla solitudine in Il comunista, di Guido Morselli - Cavallo, Stefano (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The paper aims to describe and analyze the specific loneliness of Walter Ferranini,the protagonist of Il comunista, by Guido Morselli (1976). Even though constantlysearching for success and praise – as probably it was for Guido Morselli, too – Ferraninilives his grey, unsuccessful, unhappy life in a particular way, which makes him a silent,unrecognized hero, and which gives a special “light” to the full novel.